Multicentric EORTC retrospective study shows efficacy of brentuximab vedotin in patients who have mycosis fungoides and Sézary syndrome with variable CD30 positivity. (17th August 2021) - Papadavid, E.; Kapniari, E.; Pappa, V.; Nikolaou, V.; Iliakis, T.; Dalamaga, M.; Jonak, C.; Porkert, S.; Engelina, S.; Quaglino, P.; Ortiz‐Romero, P.L.; Vico, C.; et al.
Summary: Background: Brentuximab vedotin (BV) was approved as a therapy for mycosis fungoides (MF) based on the ALCANZA trial. Little real‐world data, however, are available. Objectives: To evaluate the efficacy and safety of BV in patients with MF/Sézary Syndrome (SS) with variable CD30 positivity in a real‐world cohort and to explore potential predictors of response. Methods: Data from 72 patients with MF/SS across nine EORTC (European Organization for Research and Treatment of Cancer) centres were included. The primary endpoint was to evaluate the proportion of patients with: overall response (ORR), ORR lasting over 4 months (ORR4), time to response (TTR), response duration (RD), progression‐free survival (PFS) and time to next treatment (TTNT). Secondary aims included a safety evaluation and the association of clinicopathological features with ORR, RD and TTNT. Results: All 72 patients had received at least one systemic treatment. ORR was achieved in 45 of 67; ORR4 in 28 of 67 with a median TTR of 8 weeks [interquartile range (IQR) 5·5–14] and with a median RD of 9 months (IQR 3·4–14). Median PFS was 7 months (IQR 2–12) and median TTNT was 30 days (6–157·5). Patient response, RD, PFS and TTNT were not associated with any clinicopathological characteristics. In the MF group, patients with stage IIB/III vs. IV achieved longer PFS and had a higher percentage of ORR4. There was a statistically significant association between large‐cell transformation and skin ORR ( P  = 0·03). ORR4 was more frequently achieved in patients without lymph node involvement ( P =  0·04). Conclusions: BV is an effective option for patients with MF/SS, including those with variable CD30 positivity, large‐cell transformation, SS, longer disease duration and who have been treated previously with several therapies. Abstract : What is already known about this topic? Mycosis fungoides (MF) and Sézary syndrome (SS) are rare, heterogeneous and difficult to treat malignancies. A stage‐dependent therapeutic algorithm is used with short‐lived responses in advanced stages. Brentuximab vedotin (BV) has been recently used for the treatment of patients with MF with CD30 positivity based on the ALCANZA study but few data are available from a real‐world setting. What does this study add? This retrospective multicentric European study evaluated BV efficacy and safety in 72 patients with MF/SS and BV appeared to be an effective therapy independently from CD30 positivity and previous treatments. Patients with stage IIB and III MF achieved longer progression‐free survival and a higher percentage of overall response over 4 months (ORR4) vs. patients with stage IV MF. Patients without lymph node involvement more frequently achieved ORR4 and large‐cell transformation was significantly associated with skin ORR. Plain language summary available online